Restorable energy sources as a factor of the competitive improvement ability of a tourist destination - Gračan, Daniela (Array, 2008)
Abstract: Energy supply represents not only the energetic and ecological undertaking factor of tourist economy bearers, but the factor of profitability and competitiveness within the foreign tourist market as well. Lower energy costs form the prerequisites for higher profit accomplishments, as well as better market price competitiveness. Instead of exploiting natural resources, tourism should make the most of them, which brings into relief the directing of tourist economy subjects towards the use of restorable energy sources, particularly solar and wind energy. In spite of favourable climate features of Croatia, expressed in terms of insulation and windstrength, the restorable energy sources are still used rather insignificantly. Some positive moves in such a trend are noticeable on the island of Pag and in the town of Sibenik, where the electric energy is obtained in wind power-plants. In accordance with the concept of sustainable development of tourism, both solar energy and wind-mill energy should represent the skeleton for the energetic supply of the Croatian tourist coastline in the future. And only then, with the right amount of energy and without dependence on the world energetic markets, Croatia can develop its own healthy economic and tourist future